A bibliometric analysis of the frontiers and hotspots in chronic endometritis - Luo, Yunfang; Huang, Qin; Li, Xing; Yang, Chaogang; Ding, Jinli (Frontiers in Medicine, 2025)
BackgroundChronic endometritis (CE) is an inflammatory condition characterized by endometrial plasmacyte infiltration. The diagnosis and treatment of CE have attracted more and more attention. This article aimed to analyze the relevant keywords, development trends, and research hotspots of CE, which can provide a direction for future research.Materials and methodsThe relevant articles on CE were retrieved from the Web of Science Core Collection. VOSviewer and CiteSpase were applied to analyze publication years, countries, institutions, journals, authors, citation and co-citation, co-occurrence and citation burst of keywords.ResultsA total of 373 publications on CE were retrieved. Annual publication of articles about CE grew rapidly, and 2022 had the biggest outputs (50). USA contributed the most publications (87), and the University of Bari Aldo Moro had the highest number of articles in this field (27). The journal with the highest cited count and most publications was Fertility and Sterility (30). The main disciplines concerning the research on CE were Obstetrics Gynecology (141, 38.11%) and Reproductive Biology (126, 34.05%). Ettore Cicinelli, Kotaro Kitaya, and Dominique De Ziegler were the top three authors in publications. Except for CE and endometritis, the five most common keywords were infertility, hysteroscopy, plasma cell, recurrent implantation failure, and CD138. Pregnancy loss and recurrent miscarriage are currently within the burst period and might be the persistent research heated topics in this field.ConclusionThis study is useful for researchers to quickly grasp the current situation of CE research and enlighten researchers to explore new problems in CE.